Case report: Presumptive subcutaneous malignant peripheral nerve sheath tumor with intracranial invasion and osteolysis in the posterior fossa of a dog - Hidari, Kyosuke; Nakamoto, Yuya; Sakurai, Keiichi; Sakurai, Yoko; Nibe, Kazumi; Nakamoto, Miwa (Frontiers in Veterinary Science, 2022)
A 13-year-old castrated male Toy Poodle presented with an acute vestibular disorder. Magnetic resonance imaging and computed tomography revealed a sizeable solitary tumor in the occipital area with intracranial and extracranial lesion formation. Histopathological and immunohistochemical examinations led to a strong suspicion of malignant peripheral nerve sheath tumor. We commenced palliative treatment. However, his condition rapidly deteriorated, and he died 19 days after the onset of clinical signs. Our report is the first report of a malignant peripheral nerve sheath tumor-forming intracranial and extracranial lesions with bone destruction in dogs.